Simulation Study on the Optimization of Temperature Measurement Cable Layout in Rectangular Warehouse during Ventilation - CHU Feng-jiao; WANG Yuan-cheng; YANG Kai-min; DONG Xiao-qian (Liang you shipin ke-ji)
This study investigated the changes in grain temperature during a seven-day ventilation process in a rectangular warehouse. It also explored the optimization of the cable layout for temperature measurement. Numerical simulation was used to compare the grain temperature monitoring performance of different cable layouts, and their trade-off were evaluated through error and cost analyses. The results showed that the maximum absolute error in temperature monitoring with the national standard cable layout was 0.70 ℃, and the root mean square error was 25.83%. Uniform arrangements with adjusted cable spacing achieved a balance between accuracy and cost. In contrast, heterogeneous layouts reduced the root mean square error of grain temperature monitoring to 22.23%, while further lowering costs. In addition, the study verified the applicability of the heterogeneous layout in warehouses of different sizes. The optimized heterogeneous cable layout shows potential for practical implementation and wider adoption.